Exploring MR regression patterns in rectal cancer during neoadjuvant radiochemotherapy with daily T2- And diffusion-weighted MRI - Bostel, T.; Dreher, C.; Wollschläger, D.; Mayer, A.; König, F.; Bickelhaupt, S.; Schlemmer, H. P.; Huber, P. E.; Sterzing, F.; Bäumer, P.; Debus, J.; Nicolay, N. H. (Radiation Oncology, 2020)
Background: To date, only limited magnetic resonance imaging (MRI) data are available concerning tumor regression during neoadjuvant radiochemotherapy (RCT) of rectal cancer patients, which is a prerequisite for adaptive radiotherapy (RT) concepts. This exploratory study prospectively evaluated daily fractional MRI during neoadjuvant treatment to analyze the predictive value of MR biomarkers for treatment response. Methods: Locally advanced rectal cancer patients were examined with daily MRI during neoadjuvant RCT. Contouring of the tumor volume was performed for each MRI scan by using T2- and diffusion-weighted-imaging (DWI)-sequences. The daily apparent-diffusion coefficient (ADC) was calculated. Volumetric and functional tumor changes during RCT were analyzed and correlated with the pathological response after surgical resection. Results: In total, 171 MRI scans of eight patients were analyzed regarding anatomical and functional dynamics during RCT. Pathological complete response (pCR) could be achieved in four patients, and four patients had a pathological partial response (pPR) following neoadjuvant treatment. T2- and DWI-based volumetry proved to be statistically significant in terms of therapeutic response, and volumetric thresholds at week two and week four during RCT were defined for the prediction of pCR. In contrast, the average tumor ADC values widely overlapped between both response groups during RCT and appeared inadequate to predict treatment response in our patient cohort. Conclusion: This prospective exploratory study supports the hypothesis that MRI may be able to predict pCR of rectal cancers early during neoadjuvant RCT. Our data therefore provide a useful template to tailor future MR-guided adaptive treatment concepts.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Chemoradiotherapy; IGRT; MRI; Oncologic imaging; Pathological response; Rectal cancer